The Interconnection Between Artifacts and Realizables Entities - Fumiaki Toyoshima; Adrien Barton; Koslicki, Kathrin; Massin, Olivier (My University, 2024)
Artifacts remain nebulous entities, notwithstanding their relevance to various domains such as engineering, art and archeology. In this paper we investigate the interconnection between artifacts and realizable entities, as illustrated by dispositions, functions, and roles within the framework of the upper ontology Basic Formal Ontology (BFO). More concretely, we propose the notions of canonical artifact (something that is intentionally produced for some purpose) and usefact (something that is intended to be used for some non-original purpose) which can correspond to various usages of the term “artifact”. We also characterize them in terms of intentional realizable entities and novel realizable entities: material canonical artifacts and material usefacts can be analyzed in terms of novel intentional realizable entities and a special kind of non-novel intentional realizable entities, respectively.
Keywords: artifact; realizable entity; disposition; function; role; Basic Formal Ontology (BFO)